Heavy Metal Levels in Vegetables with Growth Stage and Plant Species Variations (Bangladesh Journal of Agricultural Research, 2012)
Field experiment was conducted to compare and investigate the concentration  levels of heavy metals in leafy vegetables with growth stage and plant species  variations on an experimental field near the net house of Soil Science Division,  Bangladesh Agricultural Research Institute, Joydebpur, Gazipur, Bangladesh  during November 2008 to January 2009. Seeds of spinach (Spinacia oleracea), red amaranth (Amaranthus tricolor) and amaranth (Amaranthus oleraseus) were  sown on 14 November 2008. Plant and soil samples were collected at different  growth stages, such as at 20, 30, 40, and 50 days after sowing (DAS). The  concentrations of lead (Pb), cadmium (Cd), nickel (Ni), cobalt (Co), and  chromium (Cr) in plant increased with the age of the plant, but the increase was  not linear. The rate of increase of concentration of these metals at 20 to 30 DAS  was found lower than that at 30 to 40 DAS, except Cr. Heavy metal content  gradually increased at the early growing stage and fall during later stages of  growth. The significant differences (P < 0.01) were observed between the mean  metal concentrations in the three vegetables species. The Pb and Co  concentrations in amaranth were found higher compared to those found in  spinach and red amaranth. Spinach exhibited higher levels of Cd and Cr than  those of other vegetables. However, the three vegetables did not differ  significantly in its Ni concentration. The order of heavy metal level in different  vegetables was Cd